Public Relation Strategyfor Improvingthe Imageofservice Qualityat Cemara Asri Pasar Buah Medan - Rahmawati, Desi; Weny (Journal Boas : Business, Economics, Accounting And Management, 2023)
This study aims to determine the public relations strategy for improving the image of service quality at Cemara Asri Fruit Market. The research method used by researchers is descriptive-qualitative research. Data collection was carried out using primary and secondary data, namely leaders at Cemara Asri Pasar Buah and also visiting customers. And the research data was also obtained from previous research, books, and internet sources. This data was collected through observation and structured interviews. Researchers use source triangulation to check the validity of research data. Data analysis in this study uses three components: data reduction, data presentation, and drawing conclusions. The results of the study show that the quality of public services at Cemara Asri Pasar Buah has implemented the Tangible, Reliability, Responsiveness, Assurance, and Empathy dimensions and their indicators. However, there are several indicators that have not gone according to the wishes of the community, including the discipline of employees in serving, namely not focusing on serving customers quickly, precisely, and dexterously.